Criminal Liability For Authentic Deed Falsification By A Notary - Afan Fakurohman (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Notary is one of the public officials (openbaar ambtenar) who is authorized to make all kinds of agreements in the form of authentic deeds, set the date, keep the deeds and issue grosses, copies and quotations, all of this as long as the act of the deed is not also required to other officials. or specifically the obligation. However, it often happens that notaries do things outside their authority, one of which is committing a criminal act of falsifying authentic deeds which results in harming other parties so that this is very disturbing and must be handled either preventively or giving criminal sanctions. The method used in this research is normative juridical, the specification of this research is descriptive analytical research. The data source uses secondary data. Data collection techniques using literature study or document study. The data analysis technique used a qualitative descriptive approach. The results of the research on the first and second conclusions. In the case of falsification of an authentic deed which is very possible to be carried out by a notary person because the authentic deed which is the product is a deed that has perfect proof before the court and cannot be denied, but if the product of the notary in the form of an authentic deed contains things that are not true then the deed is degraded into a private deed and can be declared null and void by law.